Codesigning consumer engagement strategies with ethnic minority consumers in Australian cancer services: the CanEngage Project protocol. Issue 8 (2nd August 2021) - Harrison, Reema; Walton, Merrilyn; Manias, Elizabeth; Wilson, Carlene; Girgis, Afaf; Chin, Melvin; Leone, Desiree; Seale, Holly; Smith, Allan Ben; Chauhan, Ashfaq
Abstract : Introduction: Consumer engagement is central to high-quality cancer service delivery and is a recognised strategy to minimise healthcare-associated harm. Strategies developed to enhance consumer engagement specifically in relation to preventing healthcare harm include questioning health professionals, raising concerns about possible mistakes or risks in care and encouraging patients and caregivers to report suspected errors. Patients from ethnic minority backgrounds are particularly vulnerable to unsafe care, but current engagement strategies have not been developed specifically for (and with) this population. Using an adapted approach to experience-based codesign (EBCD) to support the target population, the aim of the project is to codesign consumer engagement interventions to increase consumer engagement and safety in New South Wales and Victorian cancer inpatient, outpatient and day procedure services. Methods and analysis: A mixed-method project will be undertaken at six study sites. Our EBCD approach includes a preparatory phase in which we will provide training and support to the codesign participants, in addition to recruiting and training consumer cofacilitators for the codesign workshops. The project will follow the EBCD process of gathering and synthesising observational data from each cancer service, with interview data from consumers and staff. With the resulting in-depth understanding of the safety threats commonly experienced by ethnic minority consumers in each site, we will work through feedback events and codesign groups with consumers and staff to determine how they can be more involved with their care to minimise the potential for patient harm. Consumer engagement interventions will be coproduced in each of the six participating services that are tailored to the ethnic minority populations served. Ethics and dissemination: Ethics approval has been obtained from the Western Sydney Local Health District Human Research Ethics Committee. The project will provide strategies for ethnic minority consumers to engage with cancer services to minimise healthcare-associated harm that may be applied to diverse healthcare settings.